Updates of cancer hallmarks in patients with inborn errors of immunity. Issue 6 (21st December 2022) - Wang, Yating; Abolhassani, Hassan
Abstract : Purpose of review: The development of cancer in patients with genetically determined inborn errors of immunity (IEI) is much higher than in the general population. The hallmarks of cancer are a conceptualization tool that can refine the complexities of cancer development and pathophysiology. Each genetic defect may impose a different pathological tumor predisposition, which needs to be identified and linked with known hallmarks of cancer. Recent findings: Four new hallmarks of cancer have been suggested, recently, including unlocking phenotypic plasticity, senescent cells, nonmutational epigenetic reprogramming, and polymorphic microbiomes. Moreover, more than 50 new IEI genes have been discovered during the last 2 years from which 15 monogenic defects perturb tumor immune surveillance in patients. Summary: This review provides a more comprehensive and updated overview of all 14 cancer hallmarks in IEI patients and covers aspects of cancer predisposition in novel genes in the ever-increasing field of IEI.